2007
DOI: 10.1111/j.1365-2052.2006.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression during the onset of muscle hypertrophy in callipyge lambs

Abstract: The callipyge mutation causes postnatal muscle hypertrophy in heterozygous lambs that inherit a paternal callipyge allele (+/CLPG). Our hypothesis was that the up-regulation of one or both of the affected paternally expressed genes (DLK1 or PEG11) initiates changes in biochemical and physiological pathways in skeletal muscle to induce hypertrophy. The goal of this study was to identify changes in gene expression during the onset of muscle hypertrophy to identify the pathways that are involved in the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 43 publications
6
45
0
Order By: Relevance
“…Multiple lines of evidence suggest that the over growth of muscle mass observed in the CLPG phenotype may result from elevated expression of the DLK1 protein (4,8,30). We therefore measured Dlk1 mRNA levels in the GAST muscles of the mutant mice.…”
Section: Significancementioning
confidence: 99%
“…Multiple lines of evidence suggest that the over growth of muscle mass observed in the CLPG phenotype may result from elevated expression of the DLK1 protein (4,8,30). We therefore measured Dlk1 mRNA levels in the GAST muscles of the mutant mice.…”
Section: Significancementioning
confidence: 99%
“…qRT-PCR was performed and the amount of amplified DNA was monitored by fluorescence at the end of each cycle using CFX 96 (Bio-Rad Laboratories). Thermal cycling consisted of an initial step at 95°C for 110 s followed by 40 cycles at 95°C for 10 s and 61°C for 33 s. RPLP0 was chosen as the reference gene for normalization of all data because it was expressed more stably (Laborda, 1991;Fleming-Waddell et al, 2007;Vuocolo et al, 2007;White et al, 2008). Each qRT-PCR N. Liu et al…”
Section: Quantitative Real-time Pcr (Qrt-pcr) For Microarray Datamentioning
confidence: 99%
“…Using the Affymetrix Bovine Expression Array technique, Fleming-Waddell et al (2007) identified a particular gene expression profile in skeletal muscle of sheep carrying the callipyge mutation. Studies of gene expression profiles in sheep muscles by Lobo et al (2012) revealed differential expression of MyoD1 and IGFBP4 genes associated with breed and productive qualities.…”
Section: Introductionmentioning
confidence: 99%